2020 Grand challenge revisited: removing silos, advancing research to improve overall health - Somerman, Martha J.; Mouradian, Wendy E.; Ganesan, Sukirth M. (Frontiers in Dental Medicine, 2024)
This perspective provides strong evidence that the aims set forth when Frontiers in Dental Medicine (FDMED) was launched in 2020, to advance the integration of dental, oral, and craniofacial research with mainstream biomedical practice, underscored the value of interprofessional research collaborations, encouraging studies, publications, and commentaries in this area ripe for continued innovation. The momentum gained toward these aims must continue to inform the public, health care providers, researchers, educators, and policy makers so that they can apply the knowledge gained to improve the overall health needs of all our communities. Some suggested actions items to keep this momentum going are provided in table 1.